Topographic evolution of tidal flats based on remote sensing: an example in Jiangsu coast, Southern Yellow Sea - Kang, Yanyan; Lei, Jun; Wang, Minjing; Li, Guiping; Ding, Xianrong (Frontiers in Marine Science, 2023)
The topographic evolution of tidal flats is critical for local ecological conservation, coastal zone management, and physical oceanographic studies. However, obtaining this knowledge is often challenging due to the lack of frequently updated topographic data over large areas. With the explosion of remotely sensed data, the waterline method has become the most operational method for tidal flats topography acquisition. In this study, digital elevation models (DEMs) of the tidal flats around Tongzhou Bay of Jiangsu coast were constructed using the waterline method for three periods (2013, 2015, and 2017) before and after the construction of the Phase I reclamation project. Further, the topographic evolution characteristics were analyzed from four aspects: contours, area changes, erosion-deposition distribution, and typical cross-sections. The results showed that: (1) During the five years from 2013 to 2017, the overall tidal flats area (500km2) of Tongzhou Bay in Jiangsu coast had been in a state of deposition, with a total siltation thickness of 0.19m. (2) The reclamation activities affected the tidal flats topography quickly, but the recovery was also rapid. During the implementation of the project (2015), the area of the tidal flats above the -2m contour was rapidly reduced by 20km2, and after the completion of the project (2017), it rapidly recovered to the pre-project level. (3) The reclamation project directly affects the distribution of erosion and siltation. Outside the seawall on the east side of Yaosha sand ridge, the 0m contour expanded rapidly to the outer sea, reaching more than 250m/a. (4) The sandbars in Tongzhou Bay of Jiangsu coast generally had a southward moving trend. Over the past 40 years, the Yaosha sand ridge had shifted southward by 2500m, and the Lengjiasha sand ridge by more than 5000m. This study provides a remote sensing solution for the topographic evolution of large tidal flats under the influence of human reclamation activities.